Evidence supporting a role for the blood-cerebrospinal fluid barrier transporting circulating ghrelin into the brain - Uriarte Donati, Maia (2019)
The stomach-derived hormone ghrelin mainly acts in the brain. Studies in mice have shown that the accessibility of ghrelin into the brain is limited and that it mainly takes place in some circumventricular organs, such as the median eminence. Notably, some known brain targets of ghrelin are distantly located from the circumventricular organs. Thus, we hypothesized that ghrelin could also access the brain via the blood-cerebrospinal fluid (CSF) barrier, which consists of the choroid plexus and the hypothalamic tanycytes. Using systemic injection of ghrelin or fluorescent-ghrelin in mice, we found that cells of the blood-CSF barrier internalize these molecules. In time-response studies, we found that peripherally injected fluorescent-ghrelin quickly reaches hypothalamic regions located in apposition to the median eminence and more slowly reaches the periventricular hypothalamic parenchyma, adjacent to the dorsal part of the third ventricle. Additionally, we found that CSF ghrelin levels increase after the systemic administration of ghrelin, and that central infusions of either an anti-ghrelin antibody, which immuno-neutralizes CSF ghrelin, or a scrambled version of ghrelin, which is also internalized by cells of the blood-CSF barrier, partially impair the orexigenic effect of peripherally injected ghrelin. Thus, current evidence suggests that the blood-CSF barrier can transport circulating ghrelin into the brain, and that the access of ghrelin into the CSF is required for its full orexigenic effect.